Awareness and preparedness of dentists at handling medical emergencies in Delhi-National Capital Region - A cross-sectional survey - Pooja Dudeja; Manisha Lakhanpal Sharma; Dhirendra Srivastava; Krishan Kumar Dudeja; Vinita Dahiya; Deepak Passi (Wolters Kluwer Medknow Publications, 2021)
Context: A medical emergency (ME) may come as a surprise during our busy appointment schedules. Whether or not the office has prepared for this emergency generally decides how it will turn out. Aim: This cross-sectional survey aimed to evaluate the awareness and preparedness of dentists at handling MEs in a dental office. Settings and Design: The study was conducted over three months (December 2015 - February 2016) at two dental colleges of Delhi-National Capital Region (NCR). Materials and Methods: The total number of participants was 384, which were divided into four groups of ninety-six participants each, i.e., Group 1 (Interns); Group 2 (Academicians); Group 3 (Postgraduate students (PG)) and Group 4 (Private practitioners (PP)). Statistical Analysis: The collected data was analysed on the Statistical Package for Social Sciences (SPSS) version 20 and subjected to ANOVA and Posthoc Bonferroni tests. Results: Academicians were found to have the maximum awareness about MEs occurring in the dental office, while, interns had the minimum preparedness for the same and their difference with the other groups was statistically significant (P < 0.05). Conclusion: A huge gap exists between the awareness and preparedness of dentists at managing MEs. Sound knowledge of essential drugs reinforced by regular practical training, mock drills and properly equipped dental offices is the need of the hour.